Decent work for homeworkers in global supply chains: Existing and potential mechanisms for workercentred governance - Marlese Von Broembsen; Jenna Harvey (International Labour Organization (ILO), 2019)
As informal wage-workers who lack recognition and legal and social protections, homeworkers face a range of decent work deficits. This paper analyses the potential of existing national and global governance mechanisms to address four of these deficits for homeworkers in global supply chains: Instability and insecurity of work; unsafe working conditions; poor wages; and a lack of freedom of association and the right to collective bargaining. We construct a typology that assesses each instruments' potential to address these decent work deficits in terms of: (a) the aspects of decent work that the instrument seeks to regulate; (b) the mechanisms that the instrument relies on to ensure compliance; and (c) the extent to which the instrument is legally enforceable, and by whom. Arguing for a plural, over-overlapping concept of governance − hard and soft, operating at national, regional and international levels − we offer suggestions for improving the instruments that hold most promise for protecting homeworkers. The paper concludes that enforcement of the provisions in these instruments that protect homeworkers is contingent upon strong social movements and, most importantly, the recognition and incorporation of representative organizations of homeworkers into governance processes.
Keywords: 330